Fiber Orientation of the Transverse Carpal Ligament - Prantil, Ryan K (2011)
The transverse carpal ligament is the volar roof of the carpal tunnel. Gross observation shows that the ligament appears to have fibers that roughly orient in the transverse direction. A closer anatomical examination shows that the ligament also has oblique fibers. Knowledge of the fiber orientation of the transverse carpal ligament is valuable for further understanding the ligament's role in regulating the structural function of the carpal tunnel. The purpose of this study is to quantify collagen fiber orientation within the transverse carpal ligament using the small angle light scattering technique. Eight transverse carpal ligament samples from cadaver hands were used in this study. Individual 20 μm sections were cut evenly along the thickness of the transverse carpal ligament. Sections of three thickness levels (25%, 50%, and 75% from the volar surface) were collected for each transverse carpal ligament. Fibers were grouped in the following orientation ranges: transverse, longitudinal, oblique in the pisiform-trapezium (PT), and oblique in the scaphoid-hamate (SH) directions. In analyzing the fiber percentages, the orientation types for the different thickness levels of the ligament showed that the transverse fibers were the most prominent (>60.7%) followed by the PT oblique (18.6%), SH oblique (13.0%), and longitudinal (8.6%) fibers.